"Evaluation of Chlidren’s Behavioral Pain Reactions During Local Anesthestic Injection Using Jet Injection" (Journal of Hama University, 2021)
Aims and Objectives: To evaluate the behavioral pain reactions in children during the injection of local anesthetic using jet injection. Materials and Methods: The research sample consisted of 60 children, each child needed two injections of anesthesia by filtration on the second primary upper molars, and the sample members were divided into two groups: The first group consisted of 30 children so that we start injecting in the first session using the traditional syringe and after at least a week we perform the injection using the jet syringe and complete the appropriate treatment procedure, the second group consists of 30 children, we start in the first session with the jet syringe, and after at least a week, we perform the injection using the traditional syringe and complete the appropriate treatment procedure, and in both sessions we record a video to show it to an external monitor to record the evaluation according to the FLACC scale In addition to a self-evaluation by the child by giving him a scale of expressive faces. conclusion: It was found that the pain intensity during local injection was less when using a jet syringe than a traditional syringe.